National pastime : how Americans play baseball and the rest of the world plays soccer - Szymanski, Stefan, 1960-; Zimbalist, Andrew S. (Washington, D.C. : Brookings Institution Press, 2006)
"This revised paperback of Szymanski and Zimbalist's provocative comparison of baseball and soccer includes a new preface from the authors, updating readers through Malcolm Glazer's purchase of Manchester United and the success of the inaugural World Baseball Classic"--P. [4] of cover.
Introduction, the fields of play -- The origins of baseball and soccer leagues -- How soccer spread around the world when baseball didn't -- Pay for play : the development of the baseball and soccer labor markets -- Fans, franchises, and financial failure : why baseball clubs make money and soccer clubs don't -- Watching the money : baseball and soccer broadcasting -- Uncertain prospects : creating competitive balance -- Crossing cultures and learning lessons : what Americans need to know about world soccer and the world needs to know about American baseball.
Includes bibliographical references (p. 217-243) and index.
Keywords: Professional sports -- Economic aspects -- Cross-cultural studies; Baseball -- Economic aspects -- United States; Soccer -- Economic aspects